The role of reporting in the management of industrial enterprises on lean principles - Колос, Ірина Василівна (Technology audit and production reserves, 2016)
The article discusses the importance of reporting as a source of relevant and accurate information in the management of industrial enterprise in the context of lean changes on an ongoing basis. The main aim of research is to systematize and develop theoretical and methodological principles of formation and use of industrial enterprise reporting in order to inform about the results of change management principles and practices in the context of lean production. Retargeting of lean thinking in the management of industrial enterprise from efficiency and productivity across the value for the customer to quality and sustainable development is established based on the analysis and synthesis of scientific development. Reporting of the enterprise is grounded in historical aspect with accounting experience of its formation according to the change of lean emphasis. Condition for this is rational information support of stakeholders in management of industrial enterprise focused on financial reporting (for material losses), financial and management reporting (for fair presentation of data related to the work of staff and customer satisfaction), integrated reporting (for presenting the results of lean reforms through a combination of financial and non-financial data in logically coherent system). To determine a reporting set it should be considered: matching information needs and expectations of the general public; providing appropriate and truthful presentation of related data; logic combining of traditional quantitative-financial and non-financial indicators. Given the uniqueness of the industrial enterprises, the expediency of forming an integrated report using operating performance ratio on lean principles is proved.